Prognostic factors of hyperbaric oxygen therapy for patients with delayed encephalopathy after acute carbon monoxide poisoning. Issue 12 (December 2022) - Huang, Fangling; Yang, Lin; Tan, Zhen; Yang, Bangmin; Liu, Pingqiong; Li, Zuomin; Shi, Wanli; Peng, Kun; Yuan, Jing; He, Qing; Yang, Li; Li, Xinyu; et al.
Abstract: Delayed encephalopathy after acute carbon monoxide poisoning (DEACMP) is a disease with an incomplete pathological mechanism, long treatment time, and uncertain factors affecting the therapeutic effect. This study explored prognostic factors for DEACMP patients treated with hyperbaric oxygen therapy (HBOT) in 15 hospitals in China. The findings might provide a theoretical basis for further improving the prognosis of DEACMP patients. In this study, data from 330 patients with DEACMP who were admitted to HBOT centers of 15 hospitals in Hunan Province (China) from June 2015 to June 2020 were retrospectively analyzed, and their medical records related to disease prognosis were collected and followed up by telephone. Univariate and multivariate analyses were used to identify independent risk factors for the prognosis of DEACMP patients after HBOT. Univariate analysis revealed 11 possible prognostic factors. Consistent with univariate analysis, multivariate analysis found that underlying diseases (Odds radio(OR) = 2.886, P = 0.048), hypermyotonia (OR = 5.2558, P = 0.008), and HBOT pressure no less Than 2.3 atm absolute (ATA) ((OR = 7.812, P = 0.004) were identified as independent prognostic factors among 20 variables for poor prognosis of DEACMP patients treated with HBOT in the study. This multicenter retrospective analysis revealed that the adverse prognostic markers for DEACMP patients treated with HBOT might be underlying diseases, hypermyotonia, and an HBOT pressure of 2.3 ATA or higher. Abstract : Prognostic factors; Delayed encephalopathy after acute carbon monoxide poisoning; Hyperbaric oxygen therapy.